Image encryption algorithm based on chaotic mapping - Salleh, Mazleena (Penerbit UTM Press, 2003)
Images are routinely used in diverse areas such as medical, military, science, engineering, art, entertainment, advertising, education as well as training. With the increasing use of digital techniques for transmitting and storing images, the fundamental issue of protecting the confidentiality, integrity as well as the authenticity of images has become a major concern. This paper discusses an alternative symmetric-key encryption algorithm for securing images, namely Secure Image Encryption (SIP) that is based on chaos. Unlike other popular encryption algorithms such as Triple-DES and IDEA, SIP manipulates pixels rather than bits. Generally, SIP comprises of three main components: (1) horizontalvertical transformation function (HVT); (2) shift function (S), and (3) gray scale function (GS). HVT function is based on a two-dimensional chaotic map that utilized Baker’s map algorithm. GS function extends the algorithm to three-dimension, whereby, the third dimension refers to the level of the grayscale of a pixel. The algorithm supports two modes of operation namely Electronic Code Book (ECB) and Cipher Block Chaining (CBC). From the analysis done, SIP manage to encrypt images of various sizes even with the usage of weak keys that exist in Baker’s map encryption algorithm.